The Effect of Online Learning on Students' Mathematics Learning Motivation - Yuli Setiyani; Muhammad Irfan; Dafid Slamet Setiana (Rafandha Press, 2022)
Online learning carried out during the Covid-19 pandemic as an external factor that affects students' motivation to learn mathematics. The purpose of this study was to analyze the effect of online learning on students' learning motivation during the Covid-19 pandemic. This study uses a quantitative approach, data analysis techniques using simple linear regression analysis. The sample of this study was 60 students from class VII C and VII D at SMP N 3 Bantul, the sample was obtained by purposive sampling technique. In this study, it was found that 1) online learning had a significant effect on students' motivation to learn mathematics in learning during the Covid-19 pandemic, 2) from data analysis, it was obtained a simple linear regression equation Y = 24,154 + 0,566 X and the closeness of the relationship between the variable x (learning online) to variable Y (learning motivation) that is equal to 0.537 so it is included in the moderate category, 3) Then the contribution of variable X to variable Y can be seen from the coefficient of determination of 28.9 and the remaining 71.1% is influenced by other variables.